THE INFLUENCE OF WORK-LIFE BALANCE, ORGANIZATIONAL CULTURE, AND EMOTIONAL INTELLIGENCE ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE - Nurfiani, Aisah; Darmawan, Akhmad; Innayah, Maulida Nurul; Suyoto, Suyoto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to analyze the influence of work-life balance, organizational culture, and emotional intelligence on employee performance, with job satisfaction as an intervening variable. The study was conducted on employees of the Department of Education and Culture of Cilacap Regency. A quantitative approach was employed, using a survey method through the distribution of questionnaires. The population consisted of 120 employees, all of whom were selected as samples using a saturated sampling technique combined with purposive sampling. The data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results of the study indicate that work-life balance, organizational culture, and emotional intelligence have a positive and significant effect on job satisfaction. Job satisfaction, in turn, has a significant positive effect on employee performance. Moreover, job satisfaction is proven to significantly mediate the relationship between the three independent variables and employee performance. Enhancing work-life balance, strengthening a positive organizational culture, and developing employees' emotional intelligence can improve job satisfaction, ultimately leading to better employee performance. These findings highlight the importance of creating a balanced work environment, fostering a supportive organizational culture, and developing emotional intelligence to improve employee performance at the Department of Education and Culture of Cilacap Regency. This research is expected to contribute to the development of human resource management in government institutions